A novel Ni3N/graphene nanocomposite as supercapacitor electrode material with high capacitance and energy density1. Issue 32 (28th August 2015) - Yu, Yu; Gao, Wenyu; Shen, Zongxu; Zheng, Qing; Wu, Hao; Wang, Xi; Song, Weiguo; Ding, Kejian
<x xml:space="preserve">Abstract</x> A novel Ni3N/graphene nanocomposite has been synthesized as pseudo supercapacitor electrode material with high capacitance and energy density, due to its unique two-step oxidation/reduction reaction mechanism.